2012
DOI: 10.1007/s00134-012-2725-7
|View full text |Cite
|
Sign up to set email alerts
|

Immature platelet fraction in predicting sepsis in critically ill patients

Abstract: In patients without sepsis at ICU admission IPF% increases before sepsis becomes manifest. Measuring IPF% through an easily available technology can therefore provide an early cellular marker predicting the development of sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 33 publications
5
54
2
1
Order By: Relevance
“…Several studies have demonstrated the clinical utility of IPF in laboratory diagnosis of thrombocytopenia due to peripheral platelet destruction, particularly autoimmune thrombocytopenic purpura and thrombotic thrombocytopenic purpura [12,13]. The IPF was recently introduced as a novel diagnostic biomarker for infection and developing sepsis [14,15]. To our knowledge, however, no studies have evaluated the clinical value of IPF for coagulopathy or its prognostic value in patients with sepsis.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have demonstrated the clinical utility of IPF in laboratory diagnosis of thrombocytopenia due to peripheral platelet destruction, particularly autoimmune thrombocytopenic purpura and thrombotic thrombocytopenic purpura [12,13]. The IPF was recently introduced as a novel diagnostic biomarker for infection and developing sepsis [14,15]. To our knowledge, however, no studies have evaluated the clinical value of IPF for coagulopathy or its prognostic value in patients with sepsis.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Blasi et al [14] reported that IPF was increased before sepsis became clinically overt and was a predictor of sepsis when procalcitonin, C-reactive protein, and the white blood cell count were not. In other studies, an increased IPF was related to suspected bacterial infection and the severity of sepsis [15,27].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…It has recently been demonstrated that critically ill ICU patients have increased circulating RPs prior to the onset of sepsis [59].…”
Section: Predicting Sepsis In Critically Ill Patientsmentioning
confidence: 99%
“…They demonstrated that bone marrow aspiration yielded novel diagnoses in 22 % of patients, resulting in significant impact on management in 11 % of patients, particularly in those with absolute thrombocytopenia. De Blasi et al [81] investigated whether changes in the percentage of immature platelet fraction (IPF %) could be useful in predicting the development of sepsis over the first week of ICU stay in critically ill patients without sepsis at ICU admission. They demonstrated that significant increases in IPF values preceded the subsequent development of sepsis by a median of 2 days.…”
Section: Hematological Issues In the Critically Illmentioning
confidence: 99%